Lactobacilli and bifidobacteria promote immune homeostasis by modulating innate immune responses to human rotavirus in neonatal gnotobiotic pigs. - Anastasia N Vlasova (PLoS ONE, 2013)
The effects of co-colonization with Lactobacillus rhamnosus GG (LGG) and Bifidobacterium lactis Bb12 (Bb12) on 3-dose vaccination with attenuated HRV and challenge with virulent human rotavirus (VirHRV) were assessed in 4 groups of gnotobiotic (Gn) pigs: Pro+Vac (probiotic-colonized/vaccinated), Vac (vaccinated), Pro (probiotic-colonized, non-vaccinated) and Control (non-colonized, non-vaccinated). Subsets of pigs were euthanized pre- [post-challenge day (PCD) 0] and post (PCD7)-VirHRV challenge to assess diarrhea, fecal HRV shedding and dendritic cell/innate immune responses. Post-challenge, Pro+Vac and Vac groups were completely protected from diarrhea; protection rates against HRV shedding were 100% and 83%, respectively. Diarrhea and HRV shedding were reduced in Pro compared to Control pigs following VirHRV challenge. Diarrhea scores and virus shedding were significantly higher in Controls, compared to all other groups, coincident with significantly higher serum interferon-alpha levels post-challenge. LGG+Bb12 colonization ±vaccine promoted immunomaturation as reflected by increased frequencies of CD4, SWC3a, CD11R1, MHCII expressing mononuclear cells (MNCs) and conventional dendritic cells in intestinal tissues and blood post-challenge. Colonization decreased frequencies of toll-like receptors (TLR) 2 and TLR4 expressing MNCs from vaccinated pigs (Pro+Vac) pre-challenge and increased frequencies of TLR3 expressing MNCs from Pro pigs post-challenge, suggesting that probiotics likely exert anti-inflammatory (TLR2 and 4 down-regulation) and antiviral (TLR3 up-regulation by HRV dsRNA) actions via TLR signaling. Probiotic colonization alone (Pro) increased frequencies of intestinal and systemic apoptotic MNCs pre-challenge, thereby regulating immune hyperreactivity and tolerance. However, these frequencies were decreased in intestinal and systemic tissues post-challenge, moderating HRV-induced apoptosis. Additionally, post-challenge, Pro+Vac and Pro groups had significantly decreased MNC proliferation, suggesting that probiotics control excessive lymphoproliferative reactions upon VirHRV challenge. We conclude that in the neonatal Gn pig disease model, selected probiotics contribute to immunomaturation, regulate immune homeostasis and modulate vaccine and virulent HRV effects, thereby moderating HRV diarrhea.